Paraquat and cold tolerance in doubled haploid maize - Ambrus, Helga (Acta Biologica Szegediensis, 2008)
Paraquat and cold tolerance of doubled haploid maize plants selected and re-generated from microspores using paraquat as ROS progenitor were compared to those of non-selected DH line and the original hybrid. Three of five paraquat tolerant DH lines possess higher cold tolerance than the control DH line and the original hybrid during the termination period. On the other hand the low temperature stress (T8°C) exposed the plants at the early autotrophic phase of developments resulted in a higher cold tolerance in all of the five paraquat-selected DH lines. Our results demonstrated that the microspore-selected DH lines using paraquat as a ROS progenitors resulted not only higher tolerance against the paraquat-mediated oxidative damage, but help in the protection against the low temperature stress.